Legacy Biological Materials. (June 2015) - Klein, Robert C.; Fontes, Benjamin; Rupp, W. Dean
The recent report of improperly stored smallpox samples in freezers within laboratories from another agency on the campus of the National Institutes of Health and several other publicized issues involving highly pathogenic or regulated materials have prompted laboratories around the country to ask questions about what they might have in storage. This article describes a series of procedures initiated at Yale University to systematically evaluate and address the potential for legacy biological materials on campus. These steps are readily adaptable by other institutions.